Pengaruh Motivasi Kerja Terhadap Kinerja Karyawan Pada PT. Hasta Pusaka Sentosa Purbalingga - maharani, destin alfianika; Supriatin, Dyah; Puspitawati, Endah (Sekolah Tinggi Ilmu Ekonomi Tamansiswa Banjarnegara, 2023)
Abstract - Human resources are the main assets of the company, because to improve the efficiency and productivity of the company, it is very dependent on the performance of its human resources. The performance of human resources can be influenced by internal and external factors so that it requires a leader to be able to provide motivation. This study aims to determine the effect of work motivation on employee performance at PT. Hasta Heritage Sentosa Purbalingga. The sampling technique in this study used saturated sampling so that the research sample amounted to 30 people. The results of the study partially show existence motivation, relatedness motivation and growth motivation have no effect on employee performance. Meanwhile, simultaneously Existence motivation, Growth motivation, and relatedness motivation affect employee performance